Proposed Marketing Strategy to Achive Sustainability Company Performance for Uniquelymoz Daily - Azhaar, Nasya Yustika; Wandebori, Harimukti - (Politeknik Negeri Semarang, 2024)
The contribution of the creative industry to the Indonesian economy is targeted to continue increasing, with one of the largest contributors being the fashion subsector. The fashion industry in Indonesia is showing excellent development. Local clothing brands are starting to emerge, one of which is Uniquelymoz Daily, a fashion brand from Bandung. This article aims to develop a research model of marketing strategy to realize sustainable company performance. A literature review was conducted to build a research model that produces a framework for marketing strategy to enhance sustainable performance. The results of the study indicate that marketing strategies can be implemented by mapping the current business conditions through consumer analysis, internal and external analysis, as well as SWOT and TOWS maps. Empirical studies are needed to provide evidence of the reliability of the proposed research model.